El neumomediastino, una complicación rara de Pneumocystis Jirovecii - Daniela Neto; Jorge Cotter (Sociedade Galega de Medicina Interna, 2023)
A 39-year-old woman immunosuppressed after a bone marrow transplant due to Hodgkin's lymphoma with cure criteria but on corticotherapy for graft-versus-host disease with skin affectation and invasive ductal carcinoma of the right breast under hormone therapy. Clinically she presented with dyspnea. Laboratory workup on admission ABG PH 7.441/PCO2 37.2/PaO2 69.1 with oxygen therapy at 1 liters/minute per nasal cannula, WBC 17× 109/L, LDH 300 U/L. Respiratory viral panel is negative, Legionella urine antigen and streptococcus pneumoniae urine antigen are negative. Computed Tomography (CT) of the chest with "irregular densifications in ground glass bilaterally and multifocal consolidates with subpleural bands" (Panel A: figure A, B and C). She is admitted to the hospital for suspected opportunistic infection vs host disease with lung involvement. The etiologic study showed positive Pneumocystis Jiroveci PCR, a diagnosis of Pneumocystis Jirovecii Pneumonia was made and antibiotic therapy with trimetropin-sulfamethoxazole was initiated. On the 15th day of hospitalization due to clinical worsening he had a repeat CT scan of the chest that showed "a marked pneumomediastinum" (Panel B: figure D, E and F), the transthoracic echocardiogram excluded compression of the cardiac cavities. Pneumomediastinum is described as a rare complication of Jirovecii infection, may occur at any stage of Pneumocystis jirovecii infection. The mortality associated with this complication is high (about 50%)1. In this case, treatment was conservative with supplemental oxygen therapy, initially at 4 liters/minute with progressive decrease and gradual improvement of pneumomediastinum.